Pemanfaatan Limbah Batu Bata Klinker Sebagai Bahan Pengganti Agregat Halus dan Kasar Pada Campuran Beton - Meisyah Irawana; Dwi Talitha Salsabila; Sukarman; Dafrimon; Yurnalis, Fido (PILAR, 2024)
Concrete constitutes a blend of various constituents, including Portland cement, coarse aggregate (crushed stone),fine aggregate (sand), and water. As the availability of natural resources diminishes, the escalating demand forinfrastructure construction could lead to environmental repercussions if these resources are incessantly exploited.The region of South Sumatra, particularly in the Lubuklinggau vicinity, houses numerous red brick factories.Byproducts of these factories comprise Clinker/Scorched Brick Waste, characterized by its lightweight,impermeable, durable, and non-biodegradable nature. This study aims to effectively employ this waste to produceconcrete that is not only of superior quality but also economically viable. The research findings reveal that usingclinker brick waste to replace fine and coarse aggregates in a 28-day concrete mix: at 25% BBK, the concretepossesses an average compressive strength of 26.556 MPa; at 50% BBK, it reaches 34.882 MPa; at 75% BBK, itregisters 26.104 MPa; and at 100% BBK, it amounts to 17.55 MPa. Evidently, a remarkable surge in compressivestrength occurs at the 50% BBK variation, with a substantial 36.291% increase (34.882 MPa) compared to theaverage compressive strength of conventional concrete (25.594 MPa).